Development of a Portable Single Photon Ionization-Photoelectron Ionization Time-of-Flight Mass Spectrometer - Yunguang Huang; Jinxu Li; Bin Tang; Liping Zhu; Keyong Hou; Haiyang Li (International Journal of Analytical Chemistry)
A vacuum ultraviolet lamp based single photon ionization- (SPI-) photoelectron ionization (PEI) portable reflecting time-of-flight mass spectrometer (TOFMS) was designed for online monitoring gas samples. It has a dual mode ionization source: SPI for analyte with ionization energy (IE) below 10.6 eV and PEI for IE higher than 10.6 eV. Two kinds of sampling inlets, a capillary inlet and a membrane inlet, are utilized for high concentration and trace volatile organic compounds, respectively. A mass resolution of 1100 at m/z 64 has been obtained with a total size of 40 × 31 × 29 cm, the weight is 27 kg, and the power consumption is only 70 W. A mixture of benzene, toluene, and xylene (BTX), SO2, and discharging products of SF6 were used to test its performance, and the result showed that the limit of quantitation for BTX is as low as 5 ppbv (S/N = 10 : 1) with linear dynamic ranges greater than four orders of magnitude. The portable TOFMS was also evaluated by analyzing volatile organic compounds from wine and decomposition products of SF6 inside of a gas-insulated switchgear.